Nomenclatural notes on species of Cleistes (Orchidaceae: Vanilloideae) described by João Barbosa Rodrigues - Pansarin, Emerson Ricardo; Barros, Fábio De; Koch, Ana Kelly (Phytotaxa, 2021)
During our taxonomic study of Cleistes, we noticed that some species names published (under the genus name Pogonia) by the Brazilian botanist João Barbosa Rodrigues needed revision. In our search for type specimens, we found the holotypes of Pogonia aphylla and P. paranaensis in the herbarium of the Museu Nacional do Rio de Janeiro (R), and the holotype of P. monantha at the herbarium of the Swedish Museum of Natural History (S). The remaining type specimens housed at RB herbarium have been lost. Consequently, the designation of lectotypes for those species names is needed. Therefore, the original illustrations are here designated as lectotypes of eleven species names. Furthermore, we also propose 14 synonyms for South American Cleistes.